UPPER CUTTING TOOL TO INCREASE SLIPPER PRODUCTION IN KOTALAMA VILLAGE, KEDUNGKANDANG DISTRICT, MALANG CITY - Nuriyanti, Ika; Ingsih, Ita Suhermin; Wafi, Abdul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This community service is carried out to entrepreneurs in the slipper's home industry, precisely in Kotalama Village, Kedungkandang District, Malang City. The micro-business developing in this village manufactures slippers, which only absorbs 3 to 6 workers. IRT "Fla.Fe" was made as a partner because it has problems producing sandals, which are still very simple. Equipment not touched by science and technology has resulted in production results not being maximized, so production income has not been optimal. There still needs to be more understanding about models and variations of flip-flops. So far, cutting the upper is still using the manual method, namely with hand scissors. Through the Unisma Grant (HI-ma) program, it is expected to solve existing problems by designing and making slipper upper-cutting tools to increase production results and business profits.